ANALYSING TRADITIONAL ISLAMIC BOARDING SCHOOL STUDENTS SCIENTIFIC LITERACY USING PISA FRAMEWORK - Munasprianto Ramli; Nanda Saridewi; Abdul Rifki (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
The study aims to determine the scientific literacy ability of class IPA 11th grade students at traditional Islamic boarding schools using the 2015 PISA framework. Descriptive quantitative method used for this research. The research was conducted at two traditional Islamic boarding schools in South Tangerang called the Jamiyah Islamiyah Islamic Boarding School and the Madinatunnajah Islamic Boarding School. The research sample consisted of 57 students consisting of 33 students of the Jamiyah Islamiyah Islamic Boarding School and 24 students of the Madinatunnajah Islamic Boarding School chosen using a purposive sampling technique. The written test used is a test that distributed at PISA 2012 and 2015 which focus on two main domains of PISA 2015 scientific literacy, namely the domain of competence and knowledge. The results of this study indicate that the scientific literacy skills of students in Islamic boarding schools using the 2015 PISA framework are still "low" with an average percentage of scientific literacy obtained of 29.03%.